Inscriptions in the Byzantine and post-Byzantine history and history of art (Wiesbaden)
431 sayfa
Keywords: “This volume contains the papers of the International Symposium about Byzantine and post-Byzantine epigraphy which took place at the University of Ioannina (Greece) in June 2015. This was the most important event in Byzantine epigraphy for the year 2015. Scholars and specialists from all over Europe presented papers about epigraphic traditions and boundary signs in early Byzantine epigraphy, about Byzantine inscriptions from the Parthenon, the Hephaisteion (Church of St. George) at Athens, the monasteries of Mount Athos, the Church of St. Demetrios of Thessalonica, from the wider region of Meteora and Arta and islands of Dodecanese and the Saronic Golf (Aegina), from Byzantine fortifications, metal stamps and overstruck Byzantine lead seals. There are also papers about special issues such as the contribution of epigraphy to the prosopography of Byzantine Epirus, the usage of some termini in Byzantine and post-Byzantine epigraphy (theosostos, theophylaktos, apartisis), the prosopography of the Balkans in the early Ottoman period, donors and painters in Byzantine and post-Byzantine Epirus” --